1996
DOI: 10.1177/088391159601100403
|View full text |Cite
|
Sign up to set email alerts
|

Production of K5 Polysaccharides of Different Molecular Weight by Escherichia Coli

Abstract: An investigation was made of the molecular weight of the Escherichia coli antigenic K5 polysaccharide. Two components with molecular weights of 16,000 and 1,500 were observed. The ratio of these two components depended on a lyase produced by the same E. coli. This lyase acts by a β-elimination mechanism to depolymerize the K5. At the end of the fermentation the thermally treated (to inactivate the lyase) and untreated twenty-four-hour-old cultures each contained two K5 components of different Mw, in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The K5 heparosan chain is believed to be anchored on the cell surface through lipid substitution at the reducing end of the polysaccharide to a phosphatidic acid molecule in the outer membrane of E. coli (Alexander and Schmidt, 1982; Jann and Jann, 1990). Portions of the heparosan polysaccharide can be shed from E. coli K5 through the action of K5 heparosan lyase, an enzyme originating from a bacterial phage that cleaves the heparosan chain through a β‐elimination mechanism (Hanfling et al, 1996; Manzoni et al, 1996, 2000). The gene encoding K5 lyase is integrated into the E. coli K5 DNA (Manzoni et al, 1996) and its expression may be inducible (Legoux et al, 1996; Manzoni et al, 1996, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The K5 heparosan chain is believed to be anchored on the cell surface through lipid substitution at the reducing end of the polysaccharide to a phosphatidic acid molecule in the outer membrane of E. coli (Alexander and Schmidt, 1982; Jann and Jann, 1990). Portions of the heparosan polysaccharide can be shed from E. coli K5 through the action of K5 heparosan lyase, an enzyme originating from a bacterial phage that cleaves the heparosan chain through a β‐elimination mechanism (Hanfling et al, 1996; Manzoni et al, 1996, 2000). The gene encoding K5 lyase is integrated into the E. coli K5 DNA (Manzoni et al, 1996) and its expression may be inducible (Legoux et al, 1996; Manzoni et al, 1996, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the activity of K5 lyase expressed by the Escherichia coli was affected by growth media and culture conditions. 10,15,32 However, the mechanism to control the lyase expression is not clear. It seems the lyase is present throughout the entire time course of the fermentation.…”
mentioning
confidence: 99%
“…Previous studies have shown that the K5 lyase exist in both an intracellular form and an extracellular form. 15,32 This suggests that Escherichia coli has the machinery to export the lyase to the extracellular space. A new K5 expression system would be needed that would may be effective for increasing heparosan production.…”
mentioning
confidence: 99%
See 2 more Smart Citations